If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + -1) + -6 = 0 Reorder the terms: -3(-1 + x) + -6 = 0 (-1 * -3 + x * -3) + -6 = 0 (3 + -3x) + -6 = 0 Reorder the terms: 3 + -6 + -3x = 0 Combine like terms: 3 + -6 = -3 -3 + -3x = 0 Solving -3 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -3x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -3x = 0 + 3 -3x = 0 + 3 Combine like terms: 0 + 3 = 3 -3x = 3 Divide each side by '-3'. x = -1 Simplifying x = -1
| 2(4a-3)-(2a+5)=10 | | (2z^7-6z^3+8)+(8z^6+2z^3-6z)= | | 11ab+3b^2-6ab+6b^2-13= | | x^6-8x^5+7x^6-8x^5+8= | | 4x+6=-30 | | 5x+6=-109 | | 2x^3-15x-7=0 | | w^2+3w-18= | | 164-7x=38x+19 | | 13-7x=85-21x | | 3n-2=n+14 | | 5x=4x-3x+14 | | -3,2n+4,8=5 | | x+x^3=20 | | 2x-5=x+6 | | (X^2-6)=45 | | 35-2x=7x+21 | | 4-3i=x+12yi | | 7x-4y+8.04-2.7x=5y-0.8x+2 | | 3(2x-15)=4(x+1) | | 3(2x-15)=4(4x+1) | | 2x+y-x+4yi=-1+13i | | 3(2x-15)=4(4+1) | | 5x+3yi=15+i | | 15+-3i+3iy+2x+5y=0 | | y^3-y^2+2y-2=0 | | 7x+456=23x(762-500)+76(8x+25) | | 3x+756=6x+76 | | 8+m=48 | | 21+n=31 | | 36x+2-66=49+56-9 | | x-6=66+8 |